Reliability of the Gross Motor Function Measure among children with Cerebral Palsy in India - Amit Kumar Mandal, Prakash Kumar (South Eastern European Journal of Public Health, 2025)
Introduction: Cerebral palsy is the most common motor disability in children which is a neurological disorder, often treated by healthcare professionals. Gross Motor Function Measure (GMFM) is used as a standard measure of gross motor function in children with Cerebral palsy in many countries worldwide, including India. Objectives: To check reliability of the GMFM-88 in children with cerebral palsy who belongs to Indian society. Methods: Clinical measurement study design was used. Sixty children with CP (mean age = 27.52 months, SD = ±17.2 ) were selected. Purposive sampling method was used based on Gross Motor Function Classification System level. Test-retest and interrater were used for data collection. Children were assessed using pediatric assessment format and GMFM-88 by principal investigator on 1st day and 2nd day morning(retest). Interrater was assessed on 3rd day morning. Correlation analysis of GMFM-88 test-retest and interrater were calculated using Pearson’s correlation coefficient. Internal consistency was measured by Cronbach’s alpha. Results: Study shows significant positive correlation between GMFM-88 test scores and GMFM-88 retest scores (r = 0.590, p < 0.01), indicating there is a moderate test-retest reliability. There is significant positive correlation between GMFM-88 test scores (principal investigator) and GMFM-88 scores (interrater) (r = 0.890, p <0.01), indicating there is acceptable interrater reliability. Internal consistency of the GMFM-88 is in excellent (α = 0.992) category. Conclusions: GMFM-88 may be considered as a reliable tool which is suitable to measure gross motor function among children with CP in India.